Molecular epidemiology of and genetic susceptibility to esophageal cancer. (29th September 2014) - Bajpai, Manisha; Das, Kiron M.; Lefferts, Joel; Lisovsky, Mikhail; Mashimo, Hiroshi; Phillips, Wayne A.; Srivastava, Amitabh; To, Henry
Abstract : The following, from the 12th OESO World Conference: Cancers of the Esophagus, includes commentaries on clonal evolution in Barrett's carcinogenesis; biomarkers for early detection of esophageal cancer; the role of the methylguanine methyl transferase biomarker in the management of adenocarcinoma; and the discovery of high‐risk genes in families.